Associations Between Alternative Accounting Profitability Measures and Security Returns - Lee, Cheng-Few; Zumwalt, J. Kenton (Journal of Financial and Quantitative Analysis, 1981)
Cheng-Few Lee, J. Kenton Zumwalt, Associations Between Alternative Accounting Profitability Measures and Security Returns, The Journal of Financial and Quantitative Analysis, Vol. 16, No. 1 (Mar., 1981), pp. 71-93